2013
DOI: 10.1302/0301-620x.95b10.31511
|View full text |Cite
|
Sign up to set email alerts
|

Internal fixation of intracapsular fractures of the hip using a dynamic locking plate

Abstract: A consecutive series of 320 patients with an intracapsular fracture of the hip treated with a dynamic locking plate (Targon Femoral Neck (TFN)) were reviewed. All surviving patients were followed for a minimum of two years. During the follow-up period 109 patients died. There were 112 undisplaced fractures, of which three (2.7%) developed nonunion or re-displacement and five (4.5%) developed avascular necrosis of the femoral head. Revision to an arthroplasty was required for five patients (4.5%). A further six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 19 publications
1
31
2
Order By: Relevance
“…In that study, about 50% of the fractures occurred around the distal end of the lateral plate [4]. Parker et al also showed that a secondary fracture around the plate system occurred 1.9% of patients with an intracapsular fracture of the hip [5]. On the other hand, to the best of our knowledge, peri -implant fractures after femoral osteotomy have rarely been reported.…”
Section: Discussionmentioning
confidence: 88%
“…In that study, about 50% of the fractures occurred around the distal end of the lateral plate [4]. Parker et al also showed that a secondary fracture around the plate system occurred 1.9% of patients with an intracapsular fracture of the hip [5]. On the other hand, to the best of our knowledge, peri -implant fractures after femoral osteotomy have rarely been reported.…”
Section: Discussionmentioning
confidence: 88%
“…Increased expression of PRDX produces energy reduction peroxides and superoxides, thus allowing for formation of antioxidant response (25) and elimination of free radicals. Hypoxia and ischemia cause damage to the mitochondrial function, increased oxygen free radicals, and decrease the activity of the ATP synthetase (26). The ATP synthetase on the cytomembrane surface is highly ectopic (27) in the intermediate and advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, it is generally recommended to use hip replacement in dislocated fractures (Garden stage III and IV), in order to avoid failure after internal fixation [3]. After modern locking plate fixation in displaced fractures, the conversion rate to arthroplasty is 20 %-which seems too high when compared to the low revision rates reported after arthroplasty [26]. A problem is that previous research demonstrated that observers find it difficult to discriminate between dislocated and undislocated fractures on standard plain radiographs [4].…”
Section: Discussionmentioning
confidence: 99%